Efficacy of cryoablation versus antiarrhythmic therapy for treatment of atrial fibrillation: a systematic review and meta-analysis. (25th January 2023) - Villanueva, P; Sibulo, M; David, B; Cheng, F
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Atrial fibrillation (AF) is a common arrhythmia that causes various complications if left untreated. Current primary care guidelines recommend administration of antiarrhythmic drugs (AAD) as the preferred treatment regimen for first diagnosed AF and considers ablation if there is failure of therapy. However, recent studies show the benefit of cryoablation on the initial treatment of AF. Purpose: The primary objective of this study is to determine the efficacy and the safety of cryoablation therapy over AAD as treatment regimen for atrial fibrillation. Methods: A comprehensive and relevant search of randomized controlled trials (RCT) was conducted examining the use of cryoablation as initial treatment of AF compared to AAD. Outcome measures for recurrence of atrial arrhythmias and serious adverse effects (SAEs) were extracted and analyzed using Review Manager 5.4. Fixed effects model was used initially for both outcomes; however, if there was substantial heterogeneity (I² > 50%), random effects model was then used. Results: Four studies were included in the meta-analysis with a total of 969 subjects analyzed. Initially, a fixed effect model was used to compute for the Risk Ratio (RR) which yielded RR of 0.55 [95% CI: 0.49-0.63], I²=93, p < 0.0001. Since there was substantial heterogeneity among the four RCTs, a random effects model was then used. The heterogeneity may be attributed to the difference in study designs as some of the studies involved a cross-over design. Using the random effects model, the computed RR was 0.50 [95% CI: 0.33-0.85], I²=93, p = 0.01. Hence, cryoballoon therapy is found to be more beneficial in preventing recurrence of atrial arrhythmias. This result can be interpreted as statistically significant given that the p value is < 0.05. On the other hand, the fixed effects model revealed there was no significant difference between cryoballoon therapy and AAD in terms of SAE (RR 0.80 [95%CI: 0.58-1.10], I²=0, p=0.17). SAEs included in the studies included the following but not limited to death, stroke, acute coronary syndrome, syncope, pulmonary embolism, etc. Conclusion: Cryoablation therapy is more beneficial in preventing atrial arrhythmias compared to AADs. The rate of serious adverse event is similar between cryoablation therapy and AAD.